Propensity score-matched analysis of physician-controlled wire-guided cannulation as an effective technique against difficult cannulation in endoscopic retrograde cholangiopancreatography: A retrospective study. - Han Jo Jeon; Jae Min Lee; Sun Young Yim; Hyuk Soon Choi; Eun Sun Kim; Bora Keum; Yeon Seok Seo; Yoon Tae Jeen; Hoon Jai Chun; Hong Sik Lee (PLoS ONE, 2023)
Background Advanced endoscopic retrograde cholangiopancreatography (ERCP) cannulation strategies for difficult cases could replace conventional techniques, in which assistants control guidewires. We aimed to compare the safety and efficacy of a new salvage cannulation strategy, physician-controlled wire-guided cannulation (PCWGC), with those of a conventional strategy. Methods This retrospective study included patients with naïve papillae who underwent ERCP between January 2018 and December 2020. Patients, divided into two groups, received initial cannulation using a conventional catheter. After failed cannulation, the second attempt used PCWGC and double-guidewire technique (DGT) in the new and conventional strategy groups, respectively. Propensity score-matching (PSM) analysis compared outcomes between groups. Primary outcome included overall success rate, while secondary outcomes included cannulation time, adverse events, and cannulation difficulty subgroup analysis. Results The new strategy group comprised 255 (47.6%) of 536 patients who underwent ERCP. The total cannulation success rate was 98.4% (vs. 97.2%, p = 0.318), with similar post-ERCP pancreatitis (PEP) (1.8% vs. 2.4%, p = 0.64) rates. Following 1:1 PSM, 219/438 patients were allocated to both the conventional and new strategy groups, and 46 patients from the difficult cannulation subgroup were distributed evenly among groups. No difference in overall cannulation success rate existed between the groups before (97.2% vs. 98.4%) and after PSM (96.8% vs. 98.2%). The primary cannulation success rate was higher in the conventional strategy group, while the secondary cannulation success rate was higher in the new strategy group. However, the difficult cannulation subgroup PSM results showed that only the salvage cannulation success rate was significant (9/23, 39.1% vs. 18/23, 78.3%, p = 0.007). In the difficult cannulation subgroup, the salvage cannulation success rate for PCWGC was four times higher than DGT (95% confidence interval; 1.129-14.175), with no significant difference in PEP rate (p = 0.571). Conclusions PCWGC demonstrated greater efficacy than the conventional salvage technique. PCWGC could be a safe and useful technique, especially for difficult biliary cannulation.